Modeling heritability of temperamental differences, stress reactivity, and risk for anxiety and depression: Relevance to research domain criteria (RDoC). (24th March 2021) - Clinton, Sarah M.; Shupe, Elizabeth A.; Glover, Matthew E.; Unroe, Keaton A.; McCoy, Chelsea R.; Cohen, Joshua L.; Kerman, Ilan A.
Abstract: Animal models provide important tools to study biological and environmental factors that shape brain function and behavior. These models can be effectively leveraged by drawing on concepts from the National Institute of Mental Health Research Domain Criteria (RDoC) Initiative, which aims to delineate molecular pathways and neural circuits that underpin behavioral anomalies that transcend psychiatric conditions. To study factors that contribute to individual differences in emotionality and stress reactivity, our laboratory utilized Sprague–Dawley rats that were selectively bred for differences in novelty exploration. Selective breeding for low versus high locomotor response to novelty produced rat lines that differ in behavioral domains relevant to anxiety and depression, particularly the RDoC Negative Valence domains, including acute threat, potential threat, and loss. Bred Low Novelty Responder (LR) rats, relative to their High Responder (HR) counterparts, display high levels of behavioral inhibition, conditioned and unconditioned fear, avoidance, passive stress coping, anhedonia, and psychomotor retardation. The HR/LR traits are heritable, emerge in the first weeks of life, and appear to be driven by alterations in the developing amygdala and hippocampus. Epigenomic and transcriptomic profiling in the developing and adult HR/LR brain suggest that DNA methylation and microRNAs, as well as differences in monoaminergic transmission (dopamine and serotonin in particular), contribute to their distinct behavioral phenotypes. This work exemplifies ways that animal models such as the HR/LR rats can be effectively used to study neural and molecular factors driving emotional behavior, which may pave the way toward improved understanding the neurobiological mechanisms involved in emotional disorders. Abstract : Selective breeding for low versus high locomotor response to novelty produced rat lines that differ in behavioral domains relevant to anxiety and depression. Low Novelty Responder rats show high levels of behavioral inhibition, fear, passive stress coping, and anhedonia. Molecular studies identified epigenetic and gene expression changes that contribute to these distinct behavioral phenotypes, which may aid in understanding the biological mechanisms involved in emotional disorders.